Variables Influencing Participants’ Choice of Training Institutions for Training Program - Regmi, Suman Kumar (SXC Journal, 2024)
This study compares variables influencing Participants’ choice of training institutions for participant program in Kathmandu Valley. Choice of training institutions for training program is taken as dependent variable. Costs, locations, academic career goal, training institutions affiliations and environment are independent variables. The primary sources of data are utilized to reach the opinions of respondents with respect to choice of training institution for training program in Kathmandu Valley. The survey is based on one hundred respondents. To obtain the purpose of the study, structured questionnaires are framed. The regression models are projected to trial the significance and impact of variables affecting choice of the training institutions for training program in Kathmandu Valley. The result shows that location, environment and Training Academic affiliation are positively connect to choice of training institutions for training program. It signifies that better the environment and Training Academics affiliation higher would be the choice of liked training institutions. The result also shows that more proper the location of the training institutions, greater is the chance of selecting the training institutions for training program. The regression result shows the cost, environment and training institutions affiliation have positive impact on choice of training institutions for training program. In the same manner, the beta coefficients for carrier goal and locations have significant positive impact of the selecting training institutions for training program, which is significant at 5 percent level of significance. Overall, the selecting of training institutions for training program in Kathmandu Valley is affected by the carrier goals followed by the location.